When Love Meets Money: Priming the Possession of Money Influences Mating Strategies - Li, Yi Ming; Li, Jian; Chan, Darius K.-S.; Zhang, Bo (Frontiers in Psychology, 2016)
Money is an important factor that influences the development of romantic relationships. The current paper examines how the feeling of having relatively more or less money influences human mating strategies in long-term and short-term mating contexts under the framework of evolutionary psychology. We recruited mainland Chinese college students involved in steady, heterosexual romantic relationships to participate in two experiments. In each study, we experimentally triggered participants’ feelings of having relatively more or less money and then examined their thoughts and behaviors related to mating. Results of Study 1 showed that men who were primed to feel that they had relatively more money were less satisfied with their partners’ physical attractiveness than those primed to feel that they had less money, suggesting that the subjective feeling of having more or less money may affect men’s preferences regarding the physical appearance of a mate in a long-term relationship. Interestingly, this difference was not significant for women. Results of Study 2 indicated that both men and women who were primed to feel that they had relatively more money exhibited a greater “behavioral approach tendency” toward an attractive member of the opposite sex than those primed to feel that they had less money. This finding suggests that people who feel they have relatively more money may have more interest in an attractive alternative than those who feel they have relatively less money. The differences in mating strategies between and within the genders brought about by money support the evolutionary hypothesis that individuals adopt conditional mating strategies in response to environmental conditions. These findings have both conceptual and practical implications for the psychology of evolution and romantic relationships.